Microglia heterogeneity and therapeutic strategies in Parkinson’s disease - Tian, Jing; Liu, Xuehui; Wang, Zhuoqun; Shi, Xue; Dai, Chunlei; Yang, Li (Frontiers in Immunology, 2026)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder, characterized by the progressive loss of dopaminergic neurons in the substantia nigra (SN) and the abnormal aggregation of α-synuclein (α-syn). PD exhibits features of a chronic inflammatory disease, significantly affecting peripheral organs and the central nervous system (CNS). Clinical signs include motor symptoms such as rigidity, bradykinesia, and tremor, as well as non-motor symptoms such as psychological and cognitive issues. Microglia are resident immune cells of the CNS, exhibiting high heterogeneity and playing a crucial role in the neuronal degeneration and inflammation associated with PD. In PD, microglia play dual roles: maintaining PD homeostasis by phagocytosing and clearing α-syn aggregates while simultaneously becoming dysfunctional due to aggregate overload. This dysfunction drives their transition to a pro-inflammatory phenotype, exacerbating neurotoxicity. Recently, technological advances like single-cell transcriptomics have revealed the diverse functions and changing phenotypic lineages of microglia in PD, providing new insights into their mechanisms. This review systematically describes the biological traits of microglia and their functional, spatial, genetic, and gender-related differences in PD neurodegeneration. It summarizes new intervention and treatment strategies targeting microglia, highlights recent progress and challenges in preclinical research and clinical trials, and offers guidance for developing precision therapies for PD focused on modulating microglial function.